A report of the unusual presence of Haplotaxis cf. gordioides in a terrestrial subsoil and first isotopic analysis of its trophic position - Józefowska, Agnieszka; Martin, Patrick; Schmidt, Olaf (Zootaxa, 2025)
Haplotaxis is a genus of aquatic oligochaetes for which only limited information is available on its taxonomy, distribution, habitat and diet. During a soil survey in southern Poland, specimens of Haplotaxis cf. gordioides were unexpectedly found in terrestrial mineral subsoils, isolated from any apparent water source. This discovery provides an opportunity to investigate two aspects of Haplotaxis: habitat and diet. For the first time, the predatory nature of Haplotaxis has been assessed using stable isotope analysis of carbon and nitrogen and compared with detritivorous worms. In addition, the natural habitat of this genus was reconsidered through a literature review. This new terrestrial record raises questions about the habitat preference of Haplotaxis, suggesting that their rare soil presence may be due to challenges of extraction rather than actual absence. The finding highlights our limited understanding and exploration of subsoil fauna, including macrofauna. It also provides the first independent evidence for the predatory behaviour of Haplotaxis.